(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Alcohol consumption is known to induce reproductive toxicity, leading to adverse effects on testicular morphology, sperm quality, and DNA integrity in males. Zingiber officinale (ginger), known for its antioxidant and anti-inflammatory properties, may counteract these effects. This study aimed to investigate the impact of ginger on testicular morphometry, sperm quality, and hormonal profiles in alcohol-induced toxicity. 30 male Wistar rats were divided into six groups (n=5/group). Group A (control) received normal saline. Group B was exposed to 40% alcohol (3.50 g/kg body weight) from Days 15–28. Group C received ginger (750 mg/kg) during the same period. Groups D, E, and F were treated with alcohol for 14 days, followed by low (250 mg/kg), medium (500 mg/kg), and high (750 mg/kg) doses of ginger, respectively, from Days 15–28. The study evaluated changes in body and testicular morphometry, antioxidant enzyme and hormonal changes. Semen analysis included sperm motility, count, and morphology, while sperm chromatin/DNA integrity was assessed using Aniline Blue and Toluidine Blue staining. Alcohol exposure (Group B) significantly reduced testicular weight, sperm motility, and chromatin integrity. Ginger-treated groups (C, D, and E) showed marked improvements, with Group C outperforming the control group (A) in sperm motility, antioxidant levels, and hormones. However, Group F showed distorted results similar to Group B, suggesting high-dose toxicity. Ginger improves reproductive health and mitigates alcohol-induced toxicity in a dose-dependent manner. Moderate doses show optimal benefits, while high doses may be detrimental. These findings support ginger’s potential as a natural therapeutic agent for reproductive health. Keywords: Alcohol-induced toxicity, Antioxidant, Ginger, Semen quality, Testicular morphometry Zingiber officinale.